Condylar‐Stabilized TKR May Not Fully Compensate for PCL‐Deficiency: An In Vitro Cadaver Study. Issue 10 (27th June 2019) - Willing, Ryan; Moslemian, Alireza; Yamomo, Geofrey; Wood, Thomas; Howard, James; Lanting, Brent
ABSTRACT: Increased‐congruency bearing options are widely available in numerous total knee replacement (TKR) systems, with the intended purpose of compensating for posterior‐cruciate ligament (PCL) deficiency. However, their ability to provide adequate stability in this setting has been debated. This in vitro joint simulator study measured changes in knee joint kinematics and stability during passive flexion–extension motions and simulated activities of daily living resulting from TKR with condylar‐stabilized (CS) TKR without a PCL versus cruciate‐retaining (CR) TKR. During passive flexion, the CS TKR resulted in a more posterior tibial positioning than both the intact joint and CR TKR (by 3.4 ± 1.0 mm and 4.8 ± 0.7 mm, respectively). With a posterior tibial force applied, the CS TKR tibia was again significantly more posterior than that of the intact joint and CR TKR (by 4.7 ± 1.3 mm and 5.6 ± 0.8 mm, respectively). Furthermore, there were significant differences in the anterior/posterior kinematics of both TKR with respect to intact knees during gait, and differences between the CS and CR TKR during stair ascent and descent. Overall, there appears to be a reduction in anterior–posterior stability of the PCL‐deficient CS TKR knee, suggesting that contemporary increased‐congruency bearing surface designs may not adequately compensate for the loss of the PCL. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:2172–2181, 2019